2019
DOI: 10.1177/1071100719828379
|View full text |Cite
|
Sign up to set email alerts
|

Long-term Follow-up Results of Buechel-Pappas Ankle Arthroplasty

Abstract: Background: Total ankle replacement (TAR) is gaining popularity as a treatment option for ankle osteoarthritis. Long-term implant survival is a critical outcome to determine the success of the TAR implant. The Buechel-Pappas (BP) implant is a second-generation mobile bearing implant. The aim of this study was to analyze the BP implant survivorship at 10-year follow-up, make a subanalysis between patient groups, and evaluate long-term functional outcomes. Methods: Data of 86 patients who received 101 BP implant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 32 publications
(33 reference statements)
1
14
0
Order By: Relevance
“…However, this study did not analyze the additional procedures and postoperative tibiotalar alignment, and only 17 ankles had preoperative varus or valgus deformity. Krishnapillai et al 20 observed the same BP ankle implant cohort of Doets et al 7 with more TARs (n = 101) and longer follow-up, and they reported a 10-year implant survival of preoperative neutral alignment (91%; 95% confidence interval [CI], 83%-99%), varus alignment (87%; 95% CI, 70%-100%), and valgus alignment (72%; 95% CI, 53%-91%). Although no significant difference in survival between alignment groups was reported, they recommended caution in valgus ankles compared to varus ankles.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…However, this study did not analyze the additional procedures and postoperative tibiotalar alignment, and only 17 ankles had preoperative varus or valgus deformity. Krishnapillai et al 20 observed the same BP ankle implant cohort of Doets et al 7 with more TARs (n = 101) and longer follow-up, and they reported a 10-year implant survival of preoperative neutral alignment (91%; 95% confidence interval [CI], 83%-99%), varus alignment (87%; 95% CI, 70%-100%), and valgus alignment (72%; 95% CI, 53%-91%). Although no significant difference in survival between alignment groups was reported, they recommended caution in valgus ankles compared to varus ankles.…”
Section: Discussionmentioning
confidence: 95%
“…The items “outcome of interest” and “comparability of cohorts” corresponded with the highest risk of bias across studies. Seven studies scored no stars for the item “outcome of interest,” 14,15,31,32,34,37,38 6 studies scored no stars for the item “comparability of cohorts,” 4,14,20,31,37,38 and 3 studies scored 1 of 2 stars for this item. 13,15,34 For the other items of the checklist, where a maximum of 1 star could be obtained, 2 studies did not obtain a star.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Total ankle arthroplasty (TAA) has gradually become a more common procedure for the treatment of end-stage ankle arthritis, which can eliminate pain, restore ankle functions and allow patients to continue normal daily activities after surgery. 13 However, complications of TAA, such as wear, aseptic loosening and osteolysis, are still the obstacles to the longevity of TAA, and the survival rate of TAA is still lower than that of total hip and knee arthroplasty. 2,4,5 The reasons for the lower survival rate of TAA may include improper prosthetic designs, unfamiliar surgical techniques and unsuitable patient selections.…”
Section: Introductionmentioning
confidence: 99%
“…13 However, complications of TAA, such as wear, aseptic loosening and osteolysis, are still the obstacles to the longevity of TAA, and the survival rate of TAA is still lower than that of total hip and knee arthroplasty. 2,4,5 The reasons for the lower survival rate of TAA may include improper prosthetic designs, unfamiliar surgical techniques and unsuitable patient selections. More specifically, the crucial factor for the failures of the TAA is that the artificial replacement does not completely duplicate the natural ankle joint, which has complex kinematics, contact mechanics and close interactions between muscles and ligaments.…”
Section: Introductionmentioning
confidence: 99%